2020
DOI: 10.1371/journal.pone.0231973
|View full text |Cite
|
Sign up to set email alerts
|

Effect of the level of “Candidatus Liberibacter solanacearum” infection on the development of zebra chip disease in different potato genotypes at harvest and post storage

Abstract: Potato psyllid (Bactericera cockerelli Sulc)-transmitted "Candidatus Liberibacter solanacearum" (Lso) has been negatively impacting the potato industry in the United States as well as other potato-producing countries. Lso has been linked to a condition known as zebra chip (ZC) that affects yield and quality of potato tubers. Efforts to find sources of resistance to ZC have primarily focused on greenhouse evaluations based on a single inoculation time prior to harvest. Plant response to infection, however, coul… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
1

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 58 publications
(120 reference statements)
0
5
0
1
Order By: Relevance
“…Rashidi et al (2017) observaron tolerancia relativa de algunos genotipos, comparados con Russet Burbank, porque encontraron variación significativa en la severidad de los síntomas de tubérculos sin freír y también después del freído. También, Cruzado et al (2020) encontraron varios genotipos con baja susceptibilidad a CaLso y síntomas leves de zebra chip, aunque el tiempo de infección (etapa de desarrollo) tiene efecto en el grado de resistencia. Algunos genotipos, como Russet Burbank, muestran baja susceptibilidad a CaLso, pero son altamente intolerantes a la infección, debido a la alta expresión de los síntomas.…”
Section: Discussionunclassified
“…Rashidi et al (2017) observaron tolerancia relativa de algunos genotipos, comparados con Russet Burbank, porque encontraron variación significativa en la severidad de los síntomas de tubérculos sin freír y también después del freído. También, Cruzado et al (2020) encontraron varios genotipos con baja susceptibilidad a CaLso y síntomas leves de zebra chip, aunque el tiempo de infección (etapa de desarrollo) tiene efecto en el grado de resistencia. Algunos genotipos, como Russet Burbank, muestran baja susceptibilidad a CaLso, pero son altamente intolerantes a la infección, debido a la alta expresión de los síntomas.…”
Section: Discussionunclassified
“…Six breeding clones, previously identified as resistant to ZC and/or potato psyllid, 170,174,175 and two varieties were evaluated for CLso transmission, titer, and development of ZC symptoms. 181 No significant differences were observed in CLso transmission among entries in the greenhouse, but differences in CLso titer and ZC tuber symptoms were observed among entries in the caged field evaluations following infestation with CLso-positive potato psyllids. Full-sibling breeding clones A07781-3LB and A07781-4LB were categorized as relatively resistant to CLso with lower titers and reduced raw tuber ZC symptoms following harvest and extended storage relative to other clones and varieties.…”
Section: Host Plant Resistance/tolerance To Clsomentioning
confidence: 91%
“…Six breeding clones, previously identified as resistant to ZC and/or potato psyllid, 170,174,175 and two varieties were evaluated for CLso transmission, titer, and development of ZC symptoms 181 . No significant differences were observed in CLso transmission among entries in the greenhouse, but differences in CLso titer and ZC tuber symptoms were observed among entries in the caged field evaluations following infestation with CLso‐positive potato psyllids.…”
Section: Host Plant Resistance/tolerance To Clsomentioning
confidence: 99%
“…Resistance to Lso or the potato psyllid vector has yet to be identified in or developed for commercial potato cultivars in the United States (29,66,79). However, potential sources of resistance have been found in several germplasms with wild Solanum species in their pedigree (94).…”
Section: Host Plant Resistancementioning
confidence: 99%
“…Recent studies have used symptom severity, Lso titer (29,103), and/or analytical quantification of physiological responses (109,138,139) to determine potato host susceptibility to ZC. Wallis et al (138) identified 29 genotypes that expressed few or no symptoms following Lso infection.…”
Section: Host Plant Resistancementioning
confidence: 99%